Coax-Fed Dipole-Type Applicator for Hepatic Cancer RF Ablation - Basari, Basari; Rakhmadi, Aditya; Saito, Kazuyuki (Makara Journal of Technology, 2018)
Cancer is the third leading cause of mortality in the world and is one of the most difficult diseases to detect and cure. This fact motivates us to investigate a treatment method by using radiofrequency (RF) ablation. RF ablation therapy kills cancer cells by electromagnetically heating them up. The treatment uses an applicator that is inserted into the body to heat the cells. The cancer cells are exposed to a temperature of more than 60 °C in short duration (a few seconds to a few minutes), thereby causing cell destruction locally. To ensure effective treatment, a minimally invasive method is selected so that good local temperature distribution inside the cancer cells can be achieved. In this paper, a coax-fed dipole-type applicator is proposed for interstitial irradiation technique in hepatic cell treatment. The applicator design is conducted by simulation in CST Microwave Studio to obtain an appropriate size at operating frequency of 2.45 GHz. We also consider localizing the ablation area by designing the tip of the applicator such that the main electromagnetic radiation locally exists around it. The proposed applicator is inserted into a simple phantom model of an adult human body with normal and cancerous liver cells. Both simulation and measured results show that the proposed applicator is able to operate at center frequency of 2.45 GHz in a blood droplet-type ablation zone. A temperature of 60 °C around the cancer cell can be achieved by simulation. Moreover, a square four-array applicator is analyzed to increase the ablation zone for a larger tumor cell. The simulation results show that a reasonably wider local ablation area can be achieved.